2020
DOI: 10.17219/acem/112603
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alternate irrigation of root canals with chelating agents and sodium hypochlorite on the effectiveness of smear layer removal

Abstract: Background. After the mechanical preparation of a root canal, the canal walls are covered with a smear layer. In order to deeply clean the dentinal tubules, removal of the smear layer is recommended. There is no consensus on the length of time of rinsing with chelating agents or irrigation with alternating chelating agents and sodium hypochlorite (NaOCl). Objectives. The aim of the study was to evaluate the effectiveness of smear layer removal using 4 irrigation protocols. Material and methods. We prepared 42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…A previous study conducted by the authors shows that this protocol is highly effective in removing the smear layer. 16 After removing the smear layer, the canals were irrigated with NaOCl to dissolve the exposed (due to demineralization) protein structures. For the final irrigation in group 2, NaOCl was used; NaOCl spontaneously decomposes into a hyperosmotic sodium chloride solution after a few minutes.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study conducted by the authors shows that this protocol is highly effective in removing the smear layer. 16 After removing the smear layer, the canals were irrigated with NaOCl to dissolve the exposed (due to demineralization) protein structures. For the final irrigation in group 2, NaOCl was used; NaOCl spontaneously decomposes into a hyperosmotic sodium chloride solution after a few minutes.…”
Section: Discussionmentioning
confidence: 99%
“…The question about the rinsing protocol met with a wide variety of answers. This is probably due to lack of standardization of root canal irrigation regimens [7,8,9]. This study showed that the most commonly used rinsing sequences are:…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the printed form was delivered to dental practices. The worksheet contains two sections, the first relating to the demographics and biographies of the practitioners (1)(2)(3)(4), and the second relating to the methods, tools, and resources used in endodontic treatment (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The questions in the survey were single and multiple choice; in addition, question number 17 was an open-ended question.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Removal of the smear layer in Groups 2 and 3 was achieved using double alternating irrigation with citric acid and sodium hypochlorite. The authors' previous study shows that this approach to canal irrigation is advantageous in removing the smear layer (20). Further quick rinsing of the root canals (in these groups) with citric acid was introduced in order to deactivate the sodium hypochlorite.…”
Section: Discussionmentioning
confidence: 99%